Prevalence of endoparasites and histopathological evaluation of intestine in Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) from aquaculture pond in Janti, Polanharjo District, Klaten Regency - Putri Aji Sutarni; Elisa Herawati; Agung Budiharjo (Jurnal Iktiologi Indonesia, 2021)
Parasitic disease in aquaculture brings a great challenge to fish production. Appropriate control measure and treatment can be carried out if farmers are equipped with sufficient information on the existence of infection and its consequences on fish health. This study aimed to examine the prevalence of endoparasites in the intestine of Nile tilapia (Oreochrois niloticus) and any histological changes associated with the infection. Forty fishes were collected using purposive sampling technique at two location of aquaculture ponds in Janti village from September to December 2019. Each sampling size consisted of 10% of the total fish population in the pond. Identification of parasites was performed based on their morphology according to the standard method. Three genera of nematodes were found from fishes cultured at aquaculture ponds from local farmers, but not from that of PBIAT (Hatchery and Freshwater Fish Aquaculture). The endoparasites were identified as Cichlidogyrus sp., Acanthocephalus sp., and Ceratomyxa sp. with prevalence of 25% and intensity of 1.2%. Histological sections of the intestine of fish infected with these parasites showed alteration in the mucosa layers, such as edema and extension of the mucosa. Information on the presence of endoparasites and its effect on nile tilapia culture is important for fish farmers because it can be used as reference to control fish parasites effectively. Abstrak Penyakit ikan yang disebabkan oleh parasit menjadi tantangan besar bagi produksi ikan. Langkah pengendalian dan metode pengobatan yang tepat dapat dilakukan apabila pembudidaya ikan memiliki informasi yang cukup mengenai adanya infeksi parasit dan dampaknya terhadap kesehatan ikan. Penelitian ini bertujuan untuk menghitung prevalensi endoparasit pada intestinum ikan nila (Oreochromis niloticus) dan mengetahui perubahan histologis yang berasosiasi dengan infeksi tersebut. Pengambilan sampel sebanyak 40 ikan dilakukan dengan teknik purposive sampling di dua lokasi kolam budidaya di Desa Janti pada bulan September-Desember 2019. Jumlah ikan yang diambil merupakan 10% dari total populasi ikan di tiap kolam. Identifikasi parasit dilakukan berdasarkan morfologinya sesuai dengan metode standar. Tiga genera nematoda ditemukan pada sampel ikan yang dibudidayakan di kolam budidaya warga, sedangkan sampel ikan dari kolam Perbenihan dan Budidaya Ikan Air Tawar (PBIAT) tidak mengandung parasit. Endoparasit yang teridentifikasi yaitu Cichlidogyrus sp., Acanthocephalus sp., dan Ceratomyxa sp. dengan prevalensi sebesar 25% dan intensitas sebesar 1,2%. Jaringan intestinum ikan yang terinfeksi parasit menunjukkan adanya perubahan pada lapisan mukosa berupa edema dan perluasan tunika mukosa. Informasi tentang keberadaan endoparasit dan pengaruhnya pada ikan nila sangat penting bagi para pembudidaya ikan karena dapat menjadi acuan untuk pengendalian parasit secara efektif.